"LAB SCALE PRODUCTION AND ANTIBACTERIAL POTENTIAL OF MELANIN FROM STREPTOMYCES BIKINIENSIS" - GARE SANDIP SUBHASH; KULKARNI S.W (International Journal of Pharma and Bio Sciences, 2015)
Actinomycetes were characterized by production of various pigments on natural or synthetic media. These pigments usually described in terms of various shades of blue, red, rose, yellow, green, brown and black. Streptomyces is a major group in actinomycetes as blackish brown (melanin) pigment producer. The melanin production by Streptomyces species is the key feature for the classification of the Streptomyces group. The present study was focused on production and characterization of melanin producing Streptomyces. Soil samples were collected from the Shirala region Dist-Sangli. The total 14 Actinomycete isolates were obtained from soil by performing serial dilution technique and using Glycerol asparagine agar supplemented with Cycloheximide (100µg/ml). Morphology and spore chain arrangement of isolates were studied. Out of 14 isolates 12 were suspected belong to genus Streptomyces. The primary screening of 12 isolates for melanin production was carried out on peptone yeast extract iron agar. Two isolates such as Kd8 and Kd14 showed blackish brown diffusible pigment and these isolates were taken for secondary screening by using the tyrosine agar medium. The qualitative tests for pigment melanin were carried out by inoculating in tyrosine broth supplemented with traces of chloroform and incubating at 300 C for 48 hrs. Red color was reported in tyrosine broth indicated positive melanin production. On the basis of intensity of red color seen in the tyrosine broth Kd8 was selected for further study. Out of these isolates Kd8 isolate was identified on the basis of morphological, cultural, biochemical and 16S rRNA gene sequencing as Streptomyces bikiniensis. 0.8gm/100ml pigment was extracted from peptone yeast extract iron agar. The antibacterial activity of pigment extracted from Kd8 has been investigated. The pigment from isolate kd8 showed inhibitory zone against Escherichia coli, Staphylococcus aureus, Bacillus species and Salmonella typhi.